Nephrotic Syndrome in a Child Following a Bee Sting - Aydın, Mustafa; Kabakuş, Nimet; Akarsu, Saadet; Demirol, Mustafa (Fırat University, 2006)
Bee stings have previously been implicated in the development of nephrotic syndrome, though the reported cases in the literature are poorly documented. A three-years-old girl developed generalized edema eight days after a bee sting. The physical examination and laboratory findings were relevant with nephrotic syndrome. Her serum IgE level was to be increased. Prompt remission with resolution of edema and normalization of the laboratory findings was obtained after given the corticosteroid treatment. Due to existence of association between development of nephrotic syndrome and hypersensitivity, cases of bee sting must be closely followed-up for multiple immune-mediated complications. ©2006, Fırat Üniversitesi, Tıp Fakültesi

Arı sokmaları daha önceleri nefrotik sendromun bir nedeni olarak suçlanmış olmakla birlikte, literatürde fazla sayıda olgu bildirilmemiştir. Üç yaşında kız olgu arı sokmasından sekiz gün sonra gelişen yaygın ödemleri nedeni ile başvurdu. Fizik muayene ve laboratuvar bulguları nefrotik sendrom ile uyumlu idi. Serum IgE düzeyi yüksek bulundu. Kortikosteroid tedavisinden sonra ödemlerinin hızla gerilediği ve laboratuvar bulgularının ise normale geldiği görüldü. Nefrotik sendrom gelişimi ve aşırı duyarlılık arasında ilişki olması nedeni ile arı sokması vakaları gelişebilecek bir çok immün-aracılı komplikasyonlar yönünden yakından izlenmelidir. ©2006, Fırat Üniversitesi, Tıp Fakültesi
Arı Sokması Sonrası Gelişen Nefrotik Sendrom Olgusu